Intelligent Virtual Agents 16th International Conference, IVA 2016, Los Angeles, CA, USA, September 20-23, 2016, Proceedings - Traum, David; Swartout, William; Khooshabeh, Peter; Kopp, Stefan; Scherer, Stefan; Leuski, Anton (Lecture Notes in Artificial Intelligence,, 2016)
This book constitutes the proceedings of the 16th International Conference on Intelligent Virtual Agents, IVA 2016, held in Los Angeles, CA, USA, in September 2016. The 12 full papers, 18 short papers, and 37 demo and poster papers accepted were carefully reviewed and selected from 81 submissions. IVA 2016 also includes three workshops: Workshop on Chatbots and Conversational Agents (WOCHAT), Can you feel me now? Creating Physiologically Aware Virtual Agents (PAVA), and Graphical and Robotic Embodied Agents for Therapeutic Systems, GREATS16. Intelligent Virtual Aspects (IVAs) are intelligent digital interactive characters that can communicate with humans and other agents using natural human modalities such as facial expressions, speech, gestures, and movement. They are capable of real-time perception, cognition, emotion and action that allow them to participate in dynamic social environments. Constructing and studying IVAs requires tools from a wide range of fields such as computer science, psychology, cognitive science, communication, linguistics, interactive media, human-computer interaction and artificial intelligence. .